2002
DOI: 10.2310/6650.2002.31305
|View full text |Cite
|
Sign up to set email alerts
|

Safety Evaluation of Routine Intracoronary Acetylcholine Infusion in Patients Undergoing a First Diagnostic Coronary Angiogram

Abstract: Intracoronary acetylcholine infusion is safe, but may lead to serious adverse reactions. Care should be taken especially in patients younger than 60 years of age. Routine use of acetylcholine infusion can thus only be justified if it has important prognostic significance. This has to be proven further in large prospective studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Papaverine was not as safe as acetylcholine, and bradycardia with adenosine was found to occur primarily when used in the right coronary artery. A second study reiterated the relative safety of intracoronary acetylcholine infusion in 299 patients undergoing first diagnostic coronary angiogram 24 and reported a serious adverse event rate of 0.7%, including that in obstructive coronary artery disease patients. 24 As many as 58% of patients with persistent chest pain and no obstructive coronary artery disease have abnormal endothelial coronary function, 25 and a synthesis of 15 published reports of endothelial dysfunction demonstrated an increased relative risk ratio of nearly 10-fold (95% confidence interval,7.8-12.8).…”
Section: Coronary Reactivity Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…Papaverine was not as safe as acetylcholine, and bradycardia with adenosine was found to occur primarily when used in the right coronary artery. A second study reiterated the relative safety of intracoronary acetylcholine infusion in 299 patients undergoing first diagnostic coronary angiogram 24 and reported a serious adverse event rate of 0.7%, including that in obstructive coronary artery disease patients. 24 As many as 58% of patients with persistent chest pain and no obstructive coronary artery disease have abnormal endothelial coronary function, 25 and a synthesis of 15 published reports of endothelial dysfunction demonstrated an increased relative risk ratio of nearly 10-fold (95% confidence interval,7.8-12.8).…”
Section: Coronary Reactivity Testingmentioning
confidence: 99%
“…26 Further study demonstrated that treatment and restoration of endothelial function are associated with improved outcomes. 27 Accordingly, because the significantly increased risk of major adverse events, including death, associated with endothelial dysfunction [4][5][6]26 and microvascular coronary dysfunction is relatively high (2.5% annually) 22 compared with the nonfatal adverse event rate (0.7%-2.4%) 23,24 associated with coronary reactivity testing, patients with persistent chest pain, objective evidence of myocardial ischemia, and normal coronary angiogram results should be considered for this testing when diagnostic uncertainty is present.…”
Section: Coronary Reactivity Testingmentioning
confidence: 99%
“…Especially in those patients with angiographic nonsignificant coronary stenosis, a functional acetylcholine test may give important additional information. Adverse reactions occur, especially in younger patients suffering myocardial infarction with no significant stenosis on the angiogram [72], and special care should be taken despite the fact that acetylcholine is metabolised very quickly, and nitroglycerine can be given in case of coronary spasm. Therefore, acetylcholine testing can only be justified if prognostic significance has been proven in large cohort studies.…”
Section: Alternative Tests For Intracoronary Acetylcholine Testingmentioning
confidence: 99%
“…Furthermore, the test may give insight in the actual vascular status of the patient in order to stratify his risk for future coronary events. Due to the invasive character of the intracoronary acetylcholine test and the associated risks [72], a less invasive endothelial function test which correlates with the intracoronary acetylcholine test is desirable.…”
Section: Receptor Dependent Modes Of Actionmentioning
confidence: 99%
“…Data regarding the safety of CRT has found that this diagnostic modality is at least equal to routine coronary angiogram with approximately 1 in 1,000 risk of serious adverse events [15,16]. Moreover, because the risk of fatal and non-fatal major adverse cardiac events associated with endothelial dysfunction [5,6,8,17], and MCD [17,18] is high (up to 2.5%) compared with the risk of serious and/or adverse events with CRT [15,16] (0.7%), patients with the triad of persistent chest pain, objective evidence of myocardial ischemia, and no obstructive CAD should be considered for CRT when the diagnosis is uncertain.…”
Section: Discussionmentioning
confidence: 99%